Surviving Andersonville: The Benefits of Social Networks in POW Camps - Costa, Dora L; Kahn, Matthew E (American Economic Review, 2007)
Twenty-seven percent of the Union Army prisoners captured July 1863 or later died in captivity. At Andersonville, the death rate may have been as high as 40 percent. How did men survive such horrific conditions? Using two independent datasets, we find that friends had a statistically significant positive effect on survival probabilities and that the closer the ties between friends as measured by such identifiers as ethnicity, kinship, and the same hometown, the bigger was the impact of friends on survival probabilities. (JEL N41, Z13)